Eco-Refugees: a challenge for International Law - Andrade, Natalia (2018)
Every year thousands of people see themselves in the need of leaving their homes since they are not habitable anymore due to ecological adversities. This article analyzes the situation of the eco-refugees from a legal perspective. In the first place the concept of this term is reviewed in order to consider afterwards the environmental issues that force people to move from their country of origin, and finally, their position in International Law taking into consideration the Convention on the Status of Refugees of 1951 and its additional Protocols.